PERANAN BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI RADIO REPUBLIK INDONESIA DENPASAR MELALUI MOTIVASI - Ni Made Yuli Kartika Dewi; Ni Putu Sudarsani; I Wayan Terimajaya (Jurnal Ilmiah Satyagraha, 2026)
Abstract Research objectives 1) to analyze the influence of organizational culture on employee motivation at Radio Republik Indonesia (RRI) Denpasar. 2) To analyze the influence of job satisfaction on employee motivation at Radio Republik Indonesia (RRI) Denpasar. 3) To analyze the influence of organizational culture on employee performance at Radio Republik Indonesia (RRI) Denpasar. 4) To analyze the influence of job satisfaction on employee performance at Radio Republik Indonesia (RRI) Denpasar. 5) To analyze the influence of motivation on employee performance at Radio Republik Indonesia (RRI) Denpasar. 6) To analyze the influence of organizational culture on employee performance at Radio Republik Indonesia (RRI) Denpasar through motivation. 7) To analyze the effect of job satisfaction on employee performance at Radio Republik Indonesia (RRI) Denpasar through motivation. The research location was carried out on employees of Radio Republik Indonesia (RRI) with a sample of 60 samples using a proportional random sampling technique. With Path analysis techniques. The research results show 1) Organizational culture has a direct effect on motivation. 2) Job satisfaction has a direct effect on motivation. 3) Organizational culture has a direct effect on employee performance. 4) Job satisfaction has a direct effect on employee performance. 5) Motivation has a direct effect on employee performance. 6) Motivation is able to mediate the influence of organizational culture on employee performance. 7) Motivation is able to mediate the influence of job satisfaction on employee performance.   Keywords:    organizational culture, job satisfaction, motivation and performance